A blended learning model for a 'Multimedia Systems' course. (1st January 2013) - Hoic-Bozic, Natasa; Dlab, Martina Holenko; Kušen, Ema
The course 'Multimedia Systems', offered at the Department of Informatics, received the award for the best e-learning course at the University of Rijeka in the academic year 2010/2011, being given the highest mark according to the four elements of a review. The course was taught in a blended way, combining self-paced learning, f2f classroom learning, and online learning supported by the Moodle learning management system. Bearing in mind a transition from standard f2f teaching to online learning, a sequential model of blended learning (BL) was chosen. In this paper we describe the technology for, and the methodological approach to, course design and development, as well as the results of evaluation. A survey conducted both in the academic year 2010/2011 and 2011/2012, showed that students were satisfied with the BL approach. The findings revealed that some online activities were preferred among the students, giving us guidelines for the BL model improvement.